Key government agency perspectives on location based services regulation. Issue 6 (December 2015) - Abbas, Roba; Michael, Katina; Michael, Michael; Nicholls, Rob
Abstract: The increased prevalence of location based services has raised a number of socio-technical issues, especially in respect of the privacy expectations of individuals. Although there have been assessments of the regulatory environment regarding location based services, the research presented in this article engaged key government agency stakeholders, rather than end-users. In doing so, it provides a contribution that complements the work with end users provided by others. The article also considers the policy context for location based services regulation. It does this by describing the policy-making processes in Australia in order to provide a context for the views of government agency stakeholders. The article analyses official statements received from privacy-related and emergency-related government agencies in Australia in order to assess stakeholder views.